Competing traditions: the origins and development of worker education in South Africa. (2nd September 2021) - Webster, Edward
ABSTRACT: The article provides a socio-historical account of worker education rooted in the African working class, and more specifically in the three competing strands within this tradition – the communist strand, the "workerist" strand and the "professional" strand – each linked to contesting definitions of workers' education. It details the rich history of the first two strands, with their different origins in distinctive generational moments, and then moves on to the emergence of the professional strand in the post-democracy era where the labour movement's new socio-political role is reflected in new education institutions. The different character of this newer tradition reflects the changing profile of trade union membership and a dominant emphasis on specialised training for leadership. The article ends by describing new initiatives in worker education which attempt to deal with the new challenges to the working class thrown up in the age of digitalisation and globalisation.